Great moghuls : Babur, Humayun, Akbar, Jahangir, Shah Jahan, Aurangzeb - Whyte, Ruth (Karachi Oxford University Press, 2016)
Great Moghuls is a varied collection of stories, based on the historical accounts of the Moghuls, written in simple English for young readers. You will be surprised at the wisdom and tenacity of Babur at Panipat, and thrilled by the magicians at Jahangir's court. You will admire Humayun's Tabl-e-Adl and be enchanted by his floating gardens. You will know what led to the creation of the world's most beautiful monument, the Taj Mahal, and learn how Nizam, a poor water carrier, became an emperor for half a day. And you will enjoy reading about Babur and Jahangir, dressed as common folk, mingling with their subjects.
Includes Illustrations
Keywords: Mogul Empire -- Kings and Rulers